A new species of Hirtella (Chrysobalanaceae), and redescription of a closely related taxon, from the Atlantic Forest, Brazil - Camargo Asprino, Renata; Amorim, André Márcio (Phytotaxa, 2016)
Hirtella prancei, a new species from the Brazilian Atlantic Forest, is described, illustrated and its morphological affinities with other species are discussed. The new species differs from the closely related H. hebeclada and H. santosii mainly by its indumentum on young branches and inflorescences, leaves that are usually larger with a bullate surface and greater number of secondary veins, and by its longer stipules and inflorescences. Hirtella prancei is only known from wet forests in southern Bahia State, Brazil. A more detailed morphological description and new data on distribution and habitat are also provided for H. santosii, which was based on an analysis of additional specimens.